2017
DOI: 10.1007/s00262-017-2071-2
|View full text |Cite
|
Sign up to set email alerts
|

Ipilimumab and early signs of pulmonary toxicity in patients with metastastic melanoma: a prospective observational study

Abstract: Ipilimumab, an immune checkpoint inhibitor, is approved for treatment metastastic melanoma and is a promising agent against other malignancies. There is some preliminary evidence from case reports that ipilimumab treatment may be associated with pulmonary side effects. However, data from prospective studies on ipilimumab-related pulmonary toxicity are still scarce. Serial spirometries and measurements of CO-diffusion capacity (DLCO) in patients with metastatic melanoma before and during treatment with ipilimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…In contrast, mice treated with anti-CTLA4 DVD had intact hepatic architecture, with only scarce amounts of lymphocytes present in the liver ( Figure 4B; liver section). Pulmonary toxicity has also been reported in patients receiving ipilimumab treatments (21,22). In our study, we also observed anti-CTLA4-mediated lung toxicities associated with perivascular and peribronchial lymphocyte aggregates leading to bronchiolitis and pneumonitis.…”
Section: Resultssupporting
confidence: 83%
“…In contrast, mice treated with anti-CTLA4 DVD had intact hepatic architecture, with only scarce amounts of lymphocytes present in the liver ( Figure 4B; liver section). Pulmonary toxicity has also been reported in patients receiving ipilimumab treatments (21,22). In our study, we also observed anti-CTLA4-mediated lung toxicities associated with perivascular and peribronchial lymphocyte aggregates leading to bronchiolitis and pneumonitis.…”
Section: Resultssupporting
confidence: 83%
“…Bronchoalveolar lavage (BAL) can be used in the differential diagnosis, often manifested by an increase in the proportion of lymphocytes. In addition, a prospective observational study suggested that lung function tests during treatment might be helpful for risk stratification to screen for CIP (36). Usually, a bronchoscopic biopsy is not considered, but it can be used when it is difficult to make a differential diagnosis (37).…”
Section: Months) (11)mentioning
confidence: 99%
“…Moreover, eight out of 16 patients and nine out of 12 patients in the NAIDOO et al [76] series had, initially, a lowered forced expiratory volume in 1 s and diffusing capacity of the lung for carbon monoxide (D LCO ), respectively. Otherwise, FRANZEN et al [84] prospectively followed 71 patients with melanoma treated using ipilimumab, using pulmonary function tests. These authors reported a significant decrease in forced vital capacity (FVC) (>10%) or D LCO (>15%) after 9 weeks observed in nine (24%) out of 38 patients, with one of the patients presenting with pneumonitis in a thoracic CT scan.…”
Section: Clinical Characteristics Computed Tomography Scan Findings mentioning
confidence: 99%